Evaluation Of Collection Management And Student’s Use Of Arabic Materials In Selected Nigerian Academic Libraries - Saliu A Usman; Oladimeji Abdullahi Olukade; George Osas Eromosele; Wankasi Jamiu Abdulraheem, (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2019)
The paper examines the evaluation of collection management and student’s use of Arabic materials in the four selected Academic Libraries in Nigeria. A descriptive survey research was used to carry out the investigation. The population was randomly sampled and covered all the matriculated student of the selected institutions that were registered as a library user. The questionnaires were thereafter sent to each of the institutions surveyed to facilitate prompt, high and accurate response from target population. Data were analyzed using frequency and percentages. Findings of the study showed that all the tertiary institutions libraries under study found Arabic materials readily available. Another finding in this study showed that students use the library for seeking their information needs. It has been revealed that facilities are organized for easy use. The finding showed that acquisition and collection polices were evaluated mainly to cater for students information needs. In addition, Arabic students were significantly satisfied with the library collection policy. There is a significant relationship between the libraries Arabic based services/facilities and students educational development. The study concludes that Arabic based services/ facilities can, to a considerable extent, satisfy the information needs of users. The study will benefit researchers, Arabic studies teachers, students and Islamic organization, nation-wide and internationally.